The Changing Significance of Knowledge in Planning: A Contribution to a Knowledge-Based Understanding of Planning - Zimmermann, Karsten (Raumforschung und Raumordnung | Spatial Research and Planning, 2010)
Knowledge emerged as a relevant category in spatial development but gained less attention in the planning literature. This paper seeks to raise interest for the diverse forms of knowledge that are relevant for spatial planning. It is based on concepts from the social sciences, and a conception of knowledge application in planning processes is developed. These reflections allow for different way of thinking about planning and open new opportunities for theory development in planning.
Keywords: Knowledge; Planning; Expert knowledge; Local knowledge; Decision-making